Entropy and Selection: Life as an Adaptation for Universe Replication - Michael E. Price (Complexity)
Natural selection is the strongest known antientropic process in the universe when operating at the biological level and may also operate at the cosmological level. Consideration of how biological natural selection creates adaptations may illuminate the consequences and significance of cosmological natural selection. An organismal trait is more likely to constitute an adaptation if characterized by more improbable complex order, and such order is the hallmark of biological selection. If the same is true of traits created by selection in general, then the more improbably ordered something is (i.e., the lower its entropy), the more likely it is to be a biological or cosmological adaptation. By this logic, intelligent life (as the least-entropic known entity) is more likely than black holes or anything else to be an adaptation designed by cosmological natural selection. This view contrasts with Smolin’s suggestion that black holes are an adaptation designed by cosmological natural selection and that life is the by-product of selection for black holes. Selection may be the main or only ultimate antientropic process in the universe/multiverse; that is, much or all observed order may ultimately be the product or by-product of biological and cosmological selection.